Development of Brain Structural Networks Over Age 8: A Preliminary Study Based on Diffusion Weighted Imaging - Wu, Zhanxiong; Peng, Yun; Selvaraj, Sudhakar; Schulz, Paul E.; Zhang, Yingchun (Frontiers in Aging Neuroscience, 2020)
Brain structural network changes provide key information about the aging process of the brain. Unfortunately, there has yet to be a detailed characterization of these structural networks across different age groups. Efforts to classify these networks have also been hampered by their reliance on technically limited traditional methods, which are unable to track multiple fiber orientations within a voxel and consequently are prone to false detection and artifacts. In this study, a newly developed Ensemble Average Propagator (EAP) based probabilistic tractography method was applied to construct a structural network, with the strength of the link between any two brain functional regions estimated according to the alignment of the EAP along connecting pathways. Age-related changes in the topological organization of human brain structural networks were thereby characterized across a broad age range (ages 8 to 75 years). The data from 48 healthy participants were divided into four age groups (Group 1 aged 8-15 years; Group 2 aged 25-35 years; Group 3 aged 45-55 years; and, Group 4 aged 65-75 years; N=12 per group). We found that the brain structural network continues to strengthen during later adolescence and adulthood, through the first 20-30 years of life. Older adults, aged 65-75, had a significantly less optimized topological organization in their structural network, with decreased global efficiency and increased path lengths versus subjects in other groups. This study suggests that probabilistic tractography based on EAP provides a reliable method to construct macroscale structural connectivity networks to capture the age-associated changes of brain structures.